Reduced Serum Sphingolipids Constitute a Molecular Signature of Malnutrition in Hospitalized Patients With Decompensated Cirrhosis. Issue 3 (March 2019) - Rachakonda, Vikrant; Argemi, Josepmaria; Borhani, Amir A.; Bataller, Ramon; Tevar, Amit; Behari, Jaideep
Abstract : INTRODUCTION: Malnutrition is a leading cause of morbidity and mortality in cirrhosis. Although multiple noninvasive measures of nutritional status have been studied, no consensus exists for early identification of malnutrition in cirrhosis. Serum metabolomics offers a novel approach for identifying biomarkers in multiple disease states. To characterize alterations in metabolic pathways associated with malnutrition in hospitalized cirrhotic patients and to identify biomarkers for disease prognosis. METHODS: In this cross-sectional, observational cohort study, 51 hospitalized cirrhotic patients were classified as malnourished (42.3%) or nourished (57.7%) based on low mid-arm muscle circumference and dominant handgrip strength. Anthropometric measurements and computed tomography body composition analysis were performed. Serum was collected after overnight fasting for unbiased metabolomics analysis. RESULTS: Malnourished cirrhotic patients exhibited mild reductions in skeletal muscle index, with more marked reductions in visceral fat index. Seventy-one biochemicals were significantly altered in malnourished subjects. The serum metabolite profile was significantly different between nourished and malnourished cirrhotic patients. Pathway analysis demonstrated that only sphingolipid metabolic pathways were significantly enriched in altered metabolites. Hierarchical clustering revealed that sphingolipid metabolites clustered into nourished and malnourished cohorts. Spearman analysis demonstrated multiple statistically significant correlations between sphingolipid species and Model for End-Stage Liver Disease-Sodium. Using logistic regression, we identified 8 sphingolipids that were significantly associated with malnutrition after controlling for Model for End-Stage Liver Disease-Sodium, age, and gender. CONCLUSIONS: Malnutrition in hospitalized cirrhotic patients is characterized by reductions in multiple sphingolipid species. Dysregulated sphingolipid metabolism may be involved in the pathophysiology of malnutrition in cirrhosis and potentially serve as a biomarker of nutritional status in this population.